Temperature and Electric Field Influence on the Electrical Properties of Light-Emitting Devices Comprising PEDOT:PSS/GPTMS/Zn2SIO4:Mn Composites - Feres, Flavio H. [UNESP]; Santos, Lucas Fugikawa [UNESP]; Gozzi, Giovani [UNESP] (Springer Nature, 2018)
In the present study, we analyze the influence of temperature and active layer thickness on the electrical properties of electroluminescent devices comprising a polymeric conductive blend (poly(3,4 ethylenedioxythiophene):polystyrene sulfonate, PEDOT:PSS), an inorganic electroluminescent material (manganese doped zinc orthosilicate, Zn2SiO4:Mn) and an organosilicon material (3-glicidoxypropyltrimethoxysilane, GPTMS), manufactured at different weight ratios of the component materials. The devices were obtained by depositing the active layer by drop-casting onto ITO-coated (RF-sputtering) glass substrates and thermally evaporating gold top electrodes in high vacuum. The results show that 90 wt% Zn2SiO4:Mn is required to observe high electroluminescence from the fabricated devices and that the optimum performance (turn-on voltage of 33 V, luminous efficacy of 24 cd/A and maximum luminance of almost 2000 cd/m2) was achieve for a (9.5/0.5/90) (GPTMS/PEDOT:PSS/Zn2SiO4:Mn) weight ratio. The device turn-on voltage found to be as proportional to the thickness of the active layer, indicating that the electroluminescence occurs by a field-effect mechanism. The temperature variation in the 100-300 K range allowed us to develop a theoretical model for the device operation, where the charge carrier transport in the active layer is well described by the variable range hopping model, with luminous efficacy nearby independent of the temperature.
Keywords: composite; devices; luminescence